Supervising of How to Simple Recording Micro Business Transaction - Herliansyah, Yudhi; Daito, Appolo; Marsyaf, Marsyaf; Suprapto, Suprapto; Ilyas, Meifida (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
In today's global economy, business activities can take place without distance and time limitations, business activities between countries can be conducted offline or online anywhere and anytime. The impact is the urbanization of human resources between cities and between countries, including Indonesian citizens in Malaysia, generally, they work in the informal sector such as micro businesses, but many have difficulty expanding their business because they cannot separate their business needs and personal needs. Understanding micro-business accounting helps them to understand their business sales, cash flow, and turnover. This can only be done if they know how to keep simple records of their business. Supervising how Indonesian microbusinesses in Malaysia keep simple records has the potential to enable them to run their business well and grow.